CCR7+ selected gene-modified T cells maintain a central memory phenotype and display enhanced persistence in peripheral blood in vivo - Gray Kueberuwa; Hannah Gornall; Erik Marcelo Alcantar-Orozco; Deborah Bouvier; Zainul Abedin Kapacee; Robert Edward Hawkins; David Edward Gilham (Journal for ImmunoTherapy of Cancer)
Background Adoptive T cell immunotherapy (ATCT) for cancer entails infusing patients with T cells that recognise and destroy tumour cells. Efficient engraftment of T cells and persistence in the circulation correlate with favourable clinical outcomes. T cells of early differentiation possess an increased capacity for proliferation and therefore persistence, using these cells for ATCT could therefore lead to improved clinical outcomes.Method We describe a method to enrich T cells of early differentiation status using paramagnetic beads and antibodies targeting cells expressing C-C motif chemokine receptor 7 (CCR7).Results Selection of cells expressing CCR7 enriches T cells of bearing markers of early differentiation status. This was validated through analysis of an array of surface markers and an observed reduction in effector cell functions ex vivo. CCR7 selection resulted in dramatic 83.6 and 137 fold increases in circulating levels of CD4 and CD8 T cells respectively compared to non-sorted T cells 3 weeks after adoptive transfer to NSG mice. We observed no significant difference in the engraftment levels of CCR7 or CD62L selected cells in the NSG mouse model. Comparison of cells ex vivo, however, suggests CCR7 selection is superior to CD62L selection in enriching T cells of early differentiation status.Conclusions CCR7 selection offers a means to enrich T cells of early differentiation status for ACTC. Together our data suggests that these T cells are likely to display enhanced engraftment and persistence in patients in vivo and could therefore improve therapeutic efficacy of ACTC.